Стохастический синтез робастного управления дискретно-континуальным объектом в горизонтальной плоскости - Кузнецов, Борис Иванович; Никитина, Татьяна Борисовна; Коломиец, Валерий Витальевич; Буаклин, Мохаммед Али; Кузнецова, Людмила Георгиевна; Волошко, Александр Валерьевич (НТУ "ХПИ", 2010)
This article deals with the stochastic robust control for discrete-continual plant horizontal square. A stochastic robust observer and stochastic robust regulator is use in stochastic robust control the system. The example of dynamic characteristics for such system is given.
Stochastic robust control synthesis for discrete-continual plant on horizontal square
Keywords: объект протяженный; колебания механические; колебания собственные; стабилизация; система наведения